‘Rewritten Gospel’: The Case of Caiaphas the High Priest - Reinhartz, Adele (New Testament studies, 2009)
Although the term ‘rewritten Bible’ has been used primarily of postbiblical Jewish retellings of the Hebrew Bible, the phenomenon which it describes extends to the present day, and pertains to the NT as well as the Hebrew Bible. This paper examines two examples of ‘rewritten Gospel’—Dorothy Sayers's play cycle, The Man Born to Be King (1941–2) and Sholem Asch's novel, The Nazarene (1939)—in order to argue that such postcanonical Jesus narratives should be of interest to NT scholarship just as ‘rewritten Bible’ is of interest to scholars of the Hebrew Bible.